2011
DOI: 10.1016/j.brainres.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of source memory: Unitized source information increases familiarity-based retrieval

Abstract: Source memory tests typically require subjects to make decisions about the context in which an item was encoded and are thought to depend on recollection of details from the study episode. Although it is generally believed that familiarity does not contribute to source memory, recent behavioral studies have suggested that familiarity may also support source recognition when item and source information are integrated, or “unitized”, during study (Diana, Yonelinas, and Ranganath 2008). However, an alternative ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
75
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 38 publications
15
75
4
1
Order By: Relevance
“…Our ERP findings suggest that within-modality repetition priming underlies the fluency effect associated with correct source memory decisions. Importantly, while this specific mechanism has not been demonstrated before, the mutual interpretation of our behavioral and ERP findings does not suggest a beneficial effect of fluency on source memory as implied by previous ERP studies (Diana et al, 2011;Mollison & Curran, 2012). Therefore, these findings represent an important and novel contribution to the current debate on the interplay of fluency-based processes and source memory.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our ERP findings suggest that within-modality repetition priming underlies the fluency effect associated with correct source memory decisions. Importantly, while this specific mechanism has not been demonstrated before, the mutual interpretation of our behavioral and ERP findings does not suggest a beneficial effect of fluency on source memory as implied by previous ERP studies (Diana et al, 2011;Mollison & Curran, 2012). Therefore, these findings represent an important and novel contribution to the current debate on the interplay of fluency-based processes and source memory.…”
Section: Discussionsupporting
confidence: 55%
“…Supporting the notion of beneficial familiarity effects on source memory in young adults, Diana and colleagues (Diana, Van den Boom, Yonelinas, & Ranganath, 2011) observed a mid-frontal ERP effect for correct versus incorrect source judgments. This effect was restricted to a condition emphasizing unitization of an item with its context (such as representing an object with the background color as one single unit).…”
Section: Introductionmentioning
confidence: 85%
“…However, for other events sources are encoded as separate units from the item and so memory of the event requires an association to be made between item and source. Retrieval of this integrated memory requires recollection (Diana et al 2011;Diana et al 2008;Yonelinas, 1999). In the case of the present study, itemcontext associations might have been encoded through the latter process, where weather conditions were encoded as a separate unit to the object.…”
Section: Discussionmentioning
confidence: 81%
“…However, recent behavioral (Diana, Yonelinas, & Ranganath, 2008, 2010 and electrophysiological studies (Addante, Raganath, & Yonelinas, 2012;Diana, Van den Boom, Yonelinas, & Ranganath, 2011;Ecker, Zimmer, & GrohBordin, 2007a, b;Mollison & Curran, 2012;Peters & Daum, 2009;Speer & Curran, 2007;Tibon, Ben-Zvi, & Levy, 2014;Tibon, Gronau, Scheuplein, Mecklinger, & Levy, 2014;Tibon & Levy, 2014;Tsivilis et al, 2001;Zheng, Li, Xiao, Broster, & Jiang, 2015) have found that familiarity-related processes could also contribute to source recognition (Johnson, Hashtroudi, & Lindsay, 1993;Yonelinas, 2002). In an attempt to shed light on the familiarrelated processes embedded in source memory, Diana et al (2008Diana et al ( , 2010Diana et al, 2011) investigated the impact of encoding processes on familiarity-based recognition. The authors observed that exclusively high-unitized associations--that is, item-context pairings encoded as a single unit--elicited frontal ERP old/new effects, whereas low-unitized associations only elicited recollection-related ERPs (Diana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%